Penerapan Algoritma Ternary Comma Code Pada Aplikasi Kompresi File Gambar - Nurma Ningsih; Surya Darma Nasution; Taronisokhi Zebua (Journal of Computer System and Informatics (JoSYC), 2020)
Since the discovery of a tool to capture an image (image) in the form of a camera making technological developments not only focus on the tools but also must focus on where the data is stored. The need for storage media is something that is needed in every communication tool. Data and information communication systems are not only in the form of text but can also be in the form of images, videos and audio. Image file size that is relatively larger compared to text files is one of the causes of the amount of memory used for storing image files. The size of the image file can also cause the length of time to send the image file. Image file compression process is one way that can be done to overcome the problem of image file size. Image compression is an attempt to minimize the file size or bytes of a graphic file without reducing the quality of existing images. A certain amount of storage, such as disk space or memory, makes it possible to reduce the image file size. Many algorithms that can be used to compress image file sizes include the ternary comma code algorithm that can help reduce image file sizes. The ternary comma code algorithm has a faster time space compared to other algorithms.